Association of pro-ghrelin leu72met polymorphism with acylated ghrelin level and alcohol use disorder: a preliminary study - Kaya Akyüzlü, Dilek; Özkan Kotiloğlu, Selin; Ağtaş Ertan, Ece; Doğan, Özlem; Kılıman, Berfin; Özgür İlhan, İnci (Journal of Dependence, 2022)
Objective: Multiple environmental and genetic factors contribute to the progression of alcohol use disorder (AUD). Ghrelin is one of the important elements of the brain-gut axis that has been believed to involve in the pathophysiology of addiction. This study aimed to determine whether the GHRL Leu72Met gene polymorphism has an effect on the plasma acylated ghrelin levels in alcohol addicts for the first time.Method: A sample of 50 alcohol-dependent men and 50 controls were enrolled in this study. Acylated ghrelin levels were detected by ELISA kit. The GHRL Leu72Met polymorphism was analyzed by the standard PCR-RFLP method.Results: Acylated ghrelin levels were significantly higher in AUD patients than in controls, and were lower in AUD patients with Leu72Leu than those with Leu72Met and Met72Met. After detoxification, a dramatic decrease was seen in AUD patients having Leu72Met+Met72Met. The presence of 72Met allele was also found to be associated with an increased risk of AUD in Turkish men.Conclusion: It was indicated for the first time that the GHRL Leu72Met variant was associated with higher plasma acylated levels in patients with AUD. The GHRL Leu72 allele compared to the Met72 allele seemed to be protective against AUD in Turkish men. Taken together, despite the small number of subjects evaluated, the findings in this study suggested the effect of the GHRL Leu72Met polymorphism on plasma acylated ghrelin levels and alcohol addiction.
Keywords: Alcohol use disorder; GHRL Leu72Met polymorphism; acylated ghrelin